ANALISIS PENERAPAN AKUNTANSI PADA UMKM TOKO PAKAIAN DI KECAMATAN BEKASI TIMUR BERDASARKAN KONSEP DASAR AKUNTANSI - Raisya Puspa Septiani; Viola Saresia Kusuma (BALANCING: Accountancy Journal, 2022)
This research author did in the district of East Bekasi. In connection with this research, the object is a clothing store entrepreneur. And the population in this research is 20 clothing stores in the district of East Bekasi. The problems discussed in this study are how the application of accounting in the clothing store business in the district of East Bekasi has met the basic concepts of accounting. The purpose of this study is to find out if the application of accounting carried out by clothing store entrepreneurs has fulfilled the basic concepts of accounting in running their businesses. The data collection method that the author uses is structured interviews, documentation, and observation. While the data analysis used is a descriptive method. Based on the results of research and discussion, it can be concluded that the application of accounting carried out by clothing shop entrepreneurs in the East Bekasi district has recorded accounting and bookkeeping but is carried out very simply. The recording is still not right so it is not in accordance with the basic concepts of accounting.